The promotion activities by CIMB wealth advisor for 3G ELI products / Aiman Ariff Abdul Majid - Abdul Majid, Aiman Ariff (Faculty of Business and Management, 2009)
The scope of this study was on Cimb Wealth Advisor in Kota Damansara. It focuses on determining the factors that influence the new promotion and examines the trends of new sales performance for CIMB Wealth Advisor. It covered only in CIMB Wealth Advisor department. The persons involved for this research are only staff in CIMB Wealth Advisor Kota Damansara and the researcher. This study is based on observation during the practical time period according to their daily operation.